Effectiveness of Combined Aerobic and Anaerobic Training Programs on Improving Intermittent Endurance and Anaerobic Performance in 17-20 Year Old Padel Athletes - Kurnaz, Mert; Khanina, Naila; Schwemer, Leon; Wijanarko, Roni; Romadhona, Tasya (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background: Padel is a rapidly growing racket sport with intermittent physical exertion, consisting of periods of high-intensity (anaerobic) rallies interspersed with brief recovery periods (aerobic). Athletes aged 17-20 are in a crucial phase for optimizing their physical capacity. Research Objectives: Analyzing the effectiveness of an 8-week combined aerobic and anaerobic training program on the intermittent endurance and anaerobic performance of young padel athletes aged 17-20 years. Methods: The study used a quasi-experimental design with a pre-test and post-test control group. A sample of 30 male padel athletes (mean age 18.4 ± 1.1 years) were randomly assigned to the Experimental Group (EG, n=15), who underwent combined training (1 session of moderate-intensity aerobic exercise, 2 sessions of anaerobic HIIT per week plus regular training), and the Control Group (CG, n=15), who only underwent regular training. Measurement parameters: Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1) for intermittent endurance, Repeated Sprint Ability (RSA) for repeated sprints, and Countermovement Jump (CMJ) for leg strength. Analysis used Paired t-test and Independent t-test (p < 0.05). Results: The Experimental Group showed significant improvements in Yo-Yo IR1 (p < 0.001), average RSA time (p < 0.001), and CMJ jump height (p = 0.002). The Control Group did not show significant changes in any variables (p > 0.05). Conclusion: A combined aerobic and anaerobic training program is effective in improving the key physical components that support padel performance in athletes aged 17-20 years.